2017
DOI: 10.1080/09638199.2017.1378916
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear effects of exchange rate changes on the South African bilateral trade balance

Abstract: In testing for the J-curve, previous studies have shown that the trade balance model is better fitted using cointegration and error correction mechanisms. These mechanisms are able to incorporate the short-term deterioration and the long-term improvement of the trade balancethe definition of the J-curve. However, the drawback of the established cointegration and error correction frameworks is that they assume symmetry in the equilibrium adjustment process. Incidentally, studies which have used the linear frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Likewise, Iyke and Ho (2017) detected J-curve effect for the case of Ghana when employing NARDL method on aggregate-level data during 1986Q1–2016Q3, which is not found when symmetric assumption and ARDL approach are used. Also, Iyke and Ho (2018) inspected the bilateral trade of South Africa with respect to China, Germany, India, Japan, the UK and the USA from 1998Q1 to 2016Q2. They applied both ARDL and NARDL methods: while the former helped identify J-curve effect associated with India and the UK, the latter was able to disclose J-curve effect connected with all trading partners.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, Iyke and Ho (2017) detected J-curve effect for the case of Ghana when employing NARDL method on aggregate-level data during 1986Q1–2016Q3, which is not found when symmetric assumption and ARDL approach are used. Also, Iyke and Ho (2018) inspected the bilateral trade of South Africa with respect to China, Germany, India, Japan, the UK and the USA from 1998Q1 to 2016Q2. They applied both ARDL and NARDL methods: while the former helped identify J-curve effect associated with India and the UK, the latter was able to disclose J-curve effect connected with all trading partners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the introduction of J-curve effect, much more attention has been given to investigating the short-run and long-run impacts of exchange rate on trade balance ( Bahmani-Oskooee and Mitra, 2010 ). Nonetheless, many research report insignificant results, and the existing literature has identified 2 main culprits: aggregation bias and linear assumption ( Bahmani-Oskooee et al., 2016 ; Bahmani-Oskooee and Aftab, 2018 ; Iyke and Ho, 2018 ). First, although analyzing the impact of real effective exchange rate on the trade balance of a country with the rest of the world at aggregate level can be very convenient and present valuable information about her international trade as a whole, the findings may suffer from bias ( Rose and Yellen, 1989 ; Bahmani-Oskooee and Brooks, 1999 ; Phong et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…where , α 1 , and β 1 are parameters of the model. We compute increases (positive changes) and decreases (negative changes) in oil price uncertainty by decomposing oil price uncertainty into positive and negative partial sums as follows (see Iyke and Ho, 2018b) (4)…”
Section: B Computing Positive and Negative Oil Price Uncertaintiesmentioning
confidence: 99%